2021
DOI: 10.1007/s11356-021-16736-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical waste generation and management during COVID-19 pandemic in India: challenges and possible management strategies

Abstract: The COVID-19 pandemic has resulted in the massive generation of biomedical waste (BMW) and plastic waste (PW). This sudden spike in BMW and PW has created challenges to the existing waste management infrastructure, especially in developing countries. Safe disposal of PW and BMW is essential; otherwise, this virus will lead to a waste pandemic. This paper reviews the generation of BMW and PW before and during the COVID-19 pandemic, the regulatory framework for BMW management, policy interventions for COVID-19-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 47 publications
(60 reference statements)
0
28
0
1
Order By: Relevance
“…(Datta et al 2018). • Include the environmental implications of BMW in educational curriculum to increase awareness among future generations (Dehal et al 2021).…”
Section: Bmw Control Methods During Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…(Datta et al 2018). • Include the environmental implications of BMW in educational curriculum to increase awareness among future generations (Dehal et al 2021).…”
Section: Bmw Control Methods During Covid-19mentioning
confidence: 99%
“…Alternatively, plasma gasification at 1050 °C was used for Y-BMW. Red (R-BMW), white (W-BMW), and blue (B-BMW) categories of BMW are disposed of with dry sterilization and autoclaving at minimum temperatures (Dehal et al 2021). The sudden increase in waste generation owing to COVID-19 has challenged waste management systems worldwide.…”
Section: Quantitative and Qualitative Bmw Disposal Using Incineration...mentioning
confidence: 99%
“…This translates to about 0.33 million tons of waste annually from healthcare facilities. Out of this generated waste, 544 tons per day of the waste is disposed of using different methods, while 74 tons per day is released into the environment without proper treatment [41]. A similar study by Ramteke and Sahu [42] has found that almost 28% of total waste generated is disposed of unscientifically in open areas.…”
Section: Biomedical Waste Generationmentioning
confidence: 99%
“…6. The single-use face masks, gloves, boots, PPE kits, goggles, face shields, etc., comprise mainly low-density polyethylene, polyvinyl chloride, polycarbonate, and other components, increasing the percentage of plastic content in biomedical waste [41].…”
Section: Covid-19 Pandemic Ramifications On Biomedical Wastementioning
confidence: 99%
See 1 more Smart Citation